"Always Events® "… just another quality improvement tool … or is it?. (October 2020) - Harding, L.; Park, P.; Thorniley, M.; Ellis, M.; Reed, C.; Taylor, S.; Singleton, L.; Tolley, J.; Richardson, T.
Abstract: Introduction: Always Events® are defined as "those aspects of the care experience that should always occur when patients, their family members or other care partners, and service users interact with health care professionals and the health care system". It is a quality improvement methodology that starts by asking our patients the simple question "what matters to you?" and then through coproduction, works out a way to achieve this. Methods and results: This article tells our story and highlights the value of undertaking an Always Event® within the Radiology department at Warrington and Halton Hospitals. It will demonstrate how this approach combines research, an evaluation of findings and implementation of those findings within a very short timeframe. Embedded within the article are comments from our staff, volunteers and patients which reflect upon their experiences, our limitations, the outcomes we achieved and the impact it has had upon our patients and staff. Conclusion and Implications for practice: It was important to our patients that they would be informed of how long they would wait for their examination once they booked in at x-ray reception. By undertaking an Always Event® this process is now embedded in our departments everyday activities with over 90% of our patients now being informed of their waiting time. This continued collaboration has really emphasised the value of listening to our patients, and the benefits this can lead to. It has also encouraged a positive research culture within our department (optimisation studies, working with industry, quality projects), helping to progress our profession and resulting in a quality service for our patients.